ANALISA KARAKTERISASI KOMPOSISI CAMPURAN TANAH LIAT, ALUMINA, KANJI SEBAGAI ALTERNATIF BAHAN ISOLATOR - Suluh, Sallolo (Jurusan Teknik Mesin Fakultas Sains dan Teknik Universitas Bangka Belitung, 2025)
Abstract The use of clay is mostly used to make various crafts such as flower vases, jugs and also made into pottery, bricks and roof tiles. The purpose of this study is to determine the effect of the composition of the mixture of clay, alumina and starch on the porosity, density and water content of the heat insulator cylinder. The research method used is an experimental method by making material from a mixture of clay, alumina, starch as an alternative insulator material. A series of processes are carried out in making the material. Furthermore, after the material has been successfully formed, tests are carried out on the water content, porosity, and density of the material. The results showed that the best mixture of clay, alumina and starch was obtained in sample E with a composition of 20% clay, 60% alumina, and 20% starch. The water content, porosity, and density of the mixture were 9.49%; 26.97%; and 1,514.80 kg/m^3 Key words : alumina, insulator, composition, porosity, and starch